Acute kidney injury in preterm infants with necrotizing enterocolitis. (2nd October 2019) - Bakhoum, Christine Y.; Basalely, Abby; Koppel, Robert I.; Sethna, Christine B.
Abstract: Purpose: Acute kidney injury (AKI) is an independent predictor of morbidity and mortality in critically ill infants and children. AKI develops in an estimated one-third of the neonatal intensive care unit (NICU) population; however, literature on the incidence of AKI in premature infants with a diagnosis of necrotizing enterocolitis (NEC) is limited. The objectives of this study were to describe the incidence of AKI in infants with radiographically confirmed NEC, assess these infants for independent risk factors associated with development of AKI and evaluate if the presence of AKI is associated with increased mortality. Study design: We conducted a retrospective chart review of premature infants, gestational age (GA) 23–34 weeks, who developed modified Bell's level 2 or 3 NEC while admitted to two tertiary NICUs within our health system between 2010 and 2015. AKI was defined and staged according to modified Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Results: 77 infants with Bell's level II (63.6%) and III (36.4%) NEC were studied. AKI occurred in 42.9% of infants (Stage 1: 18.2%; Stage 2: 13%; Stage 3: 11.7%). Bell's Stage III NEC, lower GA, maternal preeclampsia/eclampsia, gentamicin/vancomycin exposure, and empiric antibiotic use were independently associated with AKI. AKI was strongly associated with mortality (HR 20.3 95%CI 2.5–162.8, p = .005) in an adjusted Cox model. Conclusions: AKI is common in premature infants who develop NEC. More severe NEC was found to be an independent risk factor for AKI. Additionally, AKI in infants with NEC increases mortality risk significantly.